Saliva use in sex: Associations with use of smartphone dating applications in men who have sex with men. (March 2018) - Chow, Eric PF; Cornelisse, Vincent J; Read, Tim RH; Chen, Marcus Y; Bradshaw, Catriona S; Fairley, Christopher K
Smartphone dating applications have become a primary source for men who have sex with men (MSM) to meet sexual partners. It has been found that MSM who used smartphone dating applications are at higher risk of gonorrhoea, but the reasons remain unknown. This study aimed to investigate whether MSM who met their partners via smartphone dating applications are more likely to engage in sexual practices such as rimming (oro-anal sex), and use of partner's saliva as a lubricant, that are associated with the risk of gonorrhoea. A cross-sectional study was conducted among 1672 MSM attending the Melbourne Sexual Health Centre, Australia, between 31 July 2014 and 30 June 2015. Multivariate logistic regression was conducted to examine the associations between sources of meeting partners and the two aforementioned sexual practices. MSM who used smartphone dating applications were 1.78 (95% CI: 1.38–2.28) times more likely to get rimmed, and 1.63 (95% CI: 1.27–2.09) times more likely to use partner's saliva as a lubricant during anal sex, compared to other sources, after adjusting for age and other sources for meeting partners. These practices are highly associated with gonorrhoea.